The relationship between well-being, empathy, moral identity, and spirituality on prosocial behavior among Malaysian youth - Velusamy, Yasothaa; Ma’rof, Aini Azeqa; H. Hamsan, Hanina (Human Resource Management Academic Research Society, 2024)
This study explores the influence of well-being, empathy, moral identity, and spirituality on prosocial behavior among Malaysian youth. A quantitative approach was employed with a sample of 411 participants, using Pearson correlation and multiple regression analyses to investigate the relationships between these variables. The results revealed that moral identity was the strongest predictor of prosocial behavior, followed closely by spirituality, empathy, and well-being. These findings highlight the central role of moral identity in shaping prosocial actions, with spirituality and empathy also playing significant roles. Well-being, while slightly less influential, still contributes meaningfully to prosocial behavior by promoting emotional stability and life satisfaction. The study emphasizes the importance of fostering moral development, spiritual growth, and emotional well-being to encourage prosocial behavior in youth. Policymakers, educators, and community leaders are encouraged to implement programs that focus on these key areas to promote a more compassionate and engaged youth population.